EMPOWERMENT OF IGBO WOMEN WITH REFERENCE TO BUCHI EMECHETA’S FICTION (Journal of Pharmaceutical Negative Results, 2023)
Women all over the World are oppressed by the patriarchy centred cultural norms. Especially the miseries of black women are worse than that of all other women. As the feminists have failed to address the woes of the black women, womanists like Alice Walker supported for the liberation of the black women. Buchi Emecheta, as a black womanist writer highlights the blues and woes of the Nigerian women and also shows them the ways to prevail over their predicament.